The Interplay of Interstitial and Substitutional Copper in Zinc Oxide - Hou, Qing; Buckeridge, John; Walsh, Aron; Xie, Zijuan; Lu, You; Keal, Thomas W.; Guan, Jingcheng; Woodley, Scott M.; Catlow, C. Richard A.; Sokol, Alexey A. (Frontiers in Chemistry, 2021)
Cu impurities is reported to have significant effects on the electrical and optical properties of bulk ZnO. In this work, we study the defect properties of Cu in ZnO using hybrid quantum mechanical/molecular mechanical (QM/MM) embedded cluster calculations based on a multi-region approach that allows us to model defects at the true dilute limit, with polarisation effects described in an accurate and consistent manner. We compute the electronic structure, energetics and geometries of Cu impurities, including substitutional and interstitial configurations, and analyse their effects on the electronic structure. Under ambient conditions, CuZn is the dominant defect in the d9 state and remains electronically passive. We find, however, as we approach typical vacuum conditions, the interstitial Cu defect becomes significant and can act as an electron trap.